#### Answer

$m^{3}$

#### Work Step by Step

We know that $\sqrt[3] m^{9}=m^{3}$, because $(m^{3})^{3}=m^{3\times3}=m^{9}$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$m^{3}$

We know that $\sqrt[3] m^{9}=m^{3}$, because $(m^{3})^{3}=m^{3\times3}=m^{9}$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.